EPIDEMICS, POPULATION AND TRIBUTE IN NEW SPAIN IN THE 16TH CENTURY (Tzintzun, Revista de Estudios Históricos, 2023)
The text reviews the use that has been made of the appraisals and taxes for thereconstruction of the great population aggregates of New Spain in the first centuryof Spanish domination, with a view to determining if it is really possible tocontinue accepting as valid the almost canonicals figures presented by SherburneF. Cook and Woodrow W. Borah. Likewise, it is about understanding the nondemographicdynamics that influenced the configuration of the taxation of thetribute during the 16th century of New Spain.
Keywords: epidemics; taxation; New Spain; 16th century; demography